A study on state unit trust funds / Ariff Zainal Abidin - Zainal Abidin, Ariff
This is an analytical study done to measure performances of selected state unit trust fund which are Amanah Saham Johor and Amanah Saham Sarawak. Composite index return is selected as independent variables using Simple Linear Regression Model in order to see the relationship with the state unit trust return. Amanah Saham Nasional is included in this study as a benchmark to measure the performance of the state unit trust fund. In order to measure the performance of these trust funds, Treynor, Sharpe and Jensen models are used. These performance evaluation model will indicate the return-risk-adjusted of trust fund, relative to ASN and the market. This project paper then will be closed with some conclusions which are related to the findings obtained from those performance-evaluation models.